2013
DOI: 10.1155/2013/985743
|View full text |Cite
|
Sign up to set email alerts
|

Association of Leukotriene Gene Variants and Plasma LTB4 Levels with Coronary Artery Disease in Asian Indians

Abstract: Leukotrienes are potent inflammatory and lipid mediators that participate in atherosclerosis. We analyzed the association of Leukotriene gene (ALOX5, ALOX5AP, LTA4H, and LTC4S) polymorphisms and plasma Leukotriene B4 (LTB4) levels with coronary artery disease (CAD) in a representative cohort of Asian Indians. In all, 136 functional single nucleotide polymorphisms (SNPs) were selected using in silico tools. Forty-five polymorphic SNPs were ranked for predicted functional effect using FastSNP. Finally, 14 functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The analysis of human atherosclerotic plaque has demonstrated an abundant expression of 5-LO, ALOX5AP, LTA4H and LTC4S genes on the arterial walls in patients with cardiovascular disease [13][14][15] . Our previous study 16) and other epidemiological reports have shown that genetic variants in the LTA4H gene are associated with a higher LTB4 level 17) . Taken together, these data suggest that leukotrienes elicit an immune response by augmenting the inflammatory gene expression.…”
Section: Clinical and Biochemical Assessmentmentioning
confidence: 68%
See 2 more Smart Citations
“…The analysis of human atherosclerotic plaque has demonstrated an abundant expression of 5-LO, ALOX5AP, LTA4H and LTC4S genes on the arterial walls in patients with cardiovascular disease [13][14][15] . Our previous study 16) and other epidemiological reports have shown that genetic variants in the LTA4H gene are associated with a higher LTB4 level 17) . Taken together, these data suggest that leukotrienes elicit an immune response by augmenting the inflammatory gene expression.…”
Section: Clinical and Biochemical Assessmentmentioning
confidence: 68%
“…Our pilot genetic association study showed that the plasma LTB4 level may modulate the risk of CAD 16) . Other functional studies have demonstrated increased LTB4 production in stimulated monocytes obtained from subjects carrying Haplotype K (HapK) of the LTA4H gene 50) .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, it is postulated that intermittent hypoxia stimulates LTs synthesis and pro-inflammatory molecules derived from the 5-LO pathway and then lead to atherosclerosis, cardiac ischemia and reperfusion injury [45][46][47][48][49]. Some clinical studies have found higher urinary levels of LTE4 in patients with acute myocardial ischemia [50] and higher levels of plasmatic LTB4 in patients with coronary artery disease compared with healthy controls [51]. Nobili and colleagues [52] suggested that the vasoconstrictor and pro-inflammatory effects of chronic and acute CysLT signaling could aggravate myocardial hypoxia and inflammation during bouts of hypoxia in chronic ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another member of the leukotriene pathway, the LTA4H gene encoding leukotriene A4 hydrolase, confers a moderate risk of myocardial infarction [ 73 ]. Four single nucleotide polymorphisms (SNPs) in the LTA4H gene showed a significant association with levels of LTB4, which acts as a link to the risk of CHD [ 74 ]. In addition, the rs2540489 polymorphism in the LTA4H gene appears to be associated with ischemic stroke of the large arteries [ 75 ].…”
Section: Genetic Contribution Of the Lipoxygenase Pathwaymentioning
confidence: 99%